2011
DOI: 10.1016/j.cell.2011.03.043
|View full text |Cite
|
Sign up to set email alerts
|

Class IIa Histone Deacetylases Are Hormone-Activated Regulators of FOXO and Mammalian Glucose Homeostasis

Abstract: SUMMARY Class IIa histone deacetylases (HDACs) are signal-dependent modulators of transcription with established roles in muscle differentiation and neuronal survival. We show here that in liver, Class IIa HDACs (HDAC4, 5, and 7) are phosphorylated and excluded from the nucleus by AMPK family kinases. In response to the fasting hormone glucagon, Class IIa HDACs are rapidly dephosphorylated and translocated to the nucleus where they associate with the promoters of gluconeogenic enzymes such as G6Pase. In turn, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
483
3
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 494 publications
(503 citation statements)
references
References 64 publications
(71 reference statements)
13
483
3
4
Order By: Relevance
“…In the fasted state, and in the DBC1 KO mice, increased SIRT1 activity could result in deacetylation of PGC1␣ (21) and FOXO (28), which would also result in higher glucose production. Moreover, it is possible that DBC1 also regulates gluconeogenesis through histone deacetylase 3 (HDAC3), which is inhibited by DBC1 (16) and has been shown to promote glucose production (40,41). In addition, it could also be that changes in the levels of DBC1, or changes to its binding partners, result in alterations in the epigenetic landscape of the PEPCK promoter.…”
Section: Discussionmentioning
confidence: 99%
“…In the fasted state, and in the DBC1 KO mice, increased SIRT1 activity could result in deacetylation of PGC1␣ (21) and FOXO (28), which would also result in higher glucose production. Moreover, it is possible that DBC1 also regulates gluconeogenesis through histone deacetylase 3 (HDAC3), which is inhibited by DBC1 (16) and has been shown to promote glucose production (40,41). In addition, it could also be that changes in the levels of DBC1, or changes to its binding partners, result in alterations in the epigenetic landscape of the PEPCK promoter.…”
Section: Discussionmentioning
confidence: 99%
“…7,23,27 In addition, HDAC5 undergoes PH-induced nuclear localization in regenerating liver, 2 and this Zn-HDAC also exhibits hypoglycemia-induced nuclear localization and regulates FOXO target gene expression in other models. 28 Finally, recent studies suggest that specific metabolites modulate isoformspecific HDAC activity in vivo. 29 Together, these considerations suggest that investigating patterns of liver histone acetylation in experimental models in which PH-induced alterations in metabolism are disrupted and regeneration is impaired could further elucidate epigenetic mechanisms linking metabolism and established pro-regenerative signaling pathways to liver regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, HDAC1 is able to complex with HDAC2 to exert normal functions. In addition, HDAC4/5 recruits HDAC3 and FOXO proteins to form a complex, allowing it to be deacetylated and activated (80). It has been reported that HDAC1 is a primary regulator of FOXO in skeletal muscle and a key regulator of the atrophy.…”
Section: Acetylation Of Foxo Proteinsmentioning
confidence: 99%